Early warning platform and its potential for non-coal mine goaf monitoring based on an optical fiber sensing network - Sun, Zengrong; Liu, Tongyu; Song, Guangdong; Hu, Binxin; Jiang, Long; Sun, Zenghua; Wu, Qi; Sun, Tong; Grattan, Kenneth T V (Journal of physics. Conference series, 2018)
Remote monitoring of a mine goaf (defined as that part of the mine from which the mineral deposit has been wholly or partially removed) is challenging, to create an early warning of potential mine collapse. In this paper, optical fiber sensing technology is applied to setting up a monitoring network and from it, through data collection and analysis, an early warning platform can be developed. When the monitoring data are collected, an analysis of dynamic disaster theory is used and the potential for the occurrence of collapse potentially can be determined. This approach provides an important means to predict sudden collapse and avoid loss of life and property in the mined-out area underground. Typical field data produced show that the monitoring results mirror the actual situation seen in mines in China, showing the value of optical fiber sensing technology for accurate monitoring of mined out areas of such workings.